Economic policies compared : west and east - Kirschen, E.S. (Amsterdam : North-Holland Pub. Co. ; New York : American Elsevier Pub. Co., 1975)
The purpose of the six chapters which follow is to use the concepts approaches which have been developed in previous chapters in the analysis of economic policy changes. The purpose of this introduction is to present a classification of the forces behind these changes. The classification suggests three basic groups of reasons for policy changes. First, there are changes in the working of the economic system. Secondly, there are changes in views about the way in which the system works. Thirdly, there are changes in policy-makers' preference functions; the pattern of priorities as between different objectives alters, or wholly new objectives may emerge.
Volume 2: National and International Experiences.
Includes bibliographical references and index.
ne 29/06/2018
Loans
Keywords: Economic policy